2008
DOI: 10.1111/j.1365-2567.2007.02743.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cells induce dendritic cell‐mediated suppression via interferon‐γ‐induced IDO

Abstract: Apoptotic cells induce dendritic cell-mediated suppression via interferon-c-induced IDO IntroductionDendritic cells (DC) are professional antigen-presenting cells that play a critical role in the induction of immunity and tolerance. Regulation of these outcomes depends on several factors, such as the occurrence of specialized DC subsets and the maturation state of the DC.1-3 Immature DC (iDC) sample their local environment and efficiently capture antigen but are ineffective in T-cell priming because of their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 61 publications
(97 reference statements)
0
52
1
Order By: Relevance
“…Therefore, it is likely that RhoA induces PI3K which phosphorylates mTOR resulting in release of eIF4E, which further results in increased translation of TGF-b1 mRNA. Some studies have indicated that another mechanism whereby DC can acquire tolerogenic potential is through induction of IDO [28,29]. Our results show no upregulation of IDO upon uptake of apoptotic DC by viable DC, indicating that induction of IDO is likely not the underlying mechanism for tolerance induction (data not shown).…”
mentioning
confidence: 39%
“…Therefore, it is likely that RhoA induces PI3K which phosphorylates mTOR resulting in release of eIF4E, which further results in increased translation of TGF-b1 mRNA. Some studies have indicated that another mechanism whereby DC can acquire tolerogenic potential is through induction of IDO [28,29]. Our results show no upregulation of IDO upon uptake of apoptotic DC by viable DC, indicating that induction of IDO is likely not the underlying mechanism for tolerance induction (data not shown).…”
mentioning
confidence: 39%
“…IDO activity can be induced by TGF-β (12), and apoptotic cells can induce IDO expression in bone marrow-derived DC coculture in vitro (14,15). Thus, we hypothesized that apoptotic cells might induce IDO expression in phagocytes after engulfment in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…IDO expression can be induced in MΦs, DCs, and stromal cells by a variety of stimuli including Toll-like receptor ligation with subsequent IFN production (α and γ) and IDO functional activity is induced and enhanced by TGF-β (10,(12)(13)(14). Moreover, apoptotic cells can induce IDO in bone marrow-derived DCs by an IFN-γ-driven mechanism in vitro (15). However, it is not known what the relevance of this finding is for either apoptotic celldriven IDO expression or immune suppression in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Propagation of tolerogenic BMDCs with GM-CSF and IL-4 also results in higher production of IFN-g. 56 IFN-g production by DCs within an inflammatory environment has also been suggested to induce antiinflammatory indoleamine 2,3-dioxygenase. 57 In our preliminary studies, neutralization of IFN-g abrogated the immunosuppressive BMDC-induced protection after kidney IRI (data not shown). Future studies will be done to better understand the functional immunosuppressive role of CD11c + -derived IFN-g.…”
Section: /2mentioning
confidence: 99%